(untitled) (Journal of Enam Medical College, 2019)
Hereditary multiple exostoses is a rare autosomal dominant pediatric disorder with an incidence of about 1:50000 characterized by multiple cartilage-capped bony protuberances, called osteochondromas or exostoses, projecting from the metaphyses of long bones. It is caused by loss of function mutations in exostosin-1 and exostosin-2 genes that encode glycosyltransferase enzymes involved in the synthesis of heparan sulfate which has fundamental role in extracellular matrix formation during bone development. It commonly presents with compressive symptoms due to bony overgrowth involving all bones except calvarium and rarely transformed into malignancy. No definite treatment is available, but careful screening of these exostoses with timely referral to respective surgeon prevents long term complications and improves quality of life. J Enam Med Col 2019; 9(1): 60-63